2012
DOI: 10.1200/jco.2011.37.5923
|View full text |Cite
|
Sign up to set email alerts
|

Risk Assessment Tool for Distant Recurrence After Platinum-Based Concurrent Chemoradiation in Patients With Locally Advanced Cervical Cancer: A Korean Gynecologic Oncology Group Study

Abstract: We have developed a robust model to predict the risk of distant recurrence in patients with locally advanced cervical cancer. Further, we discussed how the selective enrichment of the patient population could facilitate clinical trials of systemic chemotherapy in locally advanced cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
57
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(64 citation statements)
references
References 35 publications
4
57
3
Order By: Relevance
“…Nevertheless, PET/CT seems to be better at identifying extrapelvic disease and nodal metastasis than conventional CT or MRI [29]. A recent study by Kang et al introduced a risk assessment model that predicted distant recurrence in LACC [30]. The authors selected four variables, including histology, tumor size, and pelvic/paraaortic lymph node metastasis on PET/CT.…”
Section: Discussionmentioning
confidence: 97%
“…Nevertheless, PET/CT seems to be better at identifying extrapelvic disease and nodal metastasis than conventional CT or MRI [29]. A recent study by Kang et al introduced a risk assessment model that predicted distant recurrence in LACC [30]. The authors selected four variables, including histology, tumor size, and pelvic/paraaortic lymph node metastasis on PET/CT.…”
Section: Discussionmentioning
confidence: 97%
“…Nomograms that have been constructed to focus on cervical cancer patients of advanced stages who are receiving concurrent chemoradiotherapy (Tseng et al, 2010;Kang et al, 2012). However, no nomogram emphasizing on patients primarily treated with surgery has been developed thus far.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, previous studies showed more accurate predictive ability of models that included qualitative imaging parameters and clinical-pathological factors compared to FIGO stage alone. However, these studies focused only on high-risk cohorts of patients with LACC treated with definitive chemoradiation-therapy 5,14 thus unable to construct a prognostic model which is, by definition, independent of treatment received. Only one previous study constructed and validated a prognostic model of clinical-pathological factors alone (with no added imaging findings) in a large cohort of cervical cancer patients including FIGO stage I to IV 8 .…”
Section: Discussionmentioning
confidence: 99%
“…Few previous reports have simultaneously analyzed the prognostic value of multiple variables (including imaging findings) in patients with cervical cancer to create a nomogram able to provide individualized prediction of outcome 59 . These nomograms which include age, histologic type, tumor size, parametrial involvement, pelvic organ invasion and LN status, have been shown to compare favorably with FIGO staging system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation